Global perspectives on human capital-intensive firms - Cezanne, Cecile, 1981-; Saglietto, Laurence (Business Science Reference, 2019)
"This book provides an advanced analysis of a widespread and valuable organizations of the modern capitalism. It also explores the evolution of human capital-intensive firms in different sectors, their internal and external organizations, their performance, and their key strengths that could be easily transferred"--